EKSTRAKSI MINYAK DARI BIJI ALPUKAT (Persea Americana Mill) MENGGUNAKAN PELARUT N-HEPTANA - Atikah Risyad, Resi Levi Permadani, Siswarni MZ (Universitas Sumatera Utara, 2016)
Avocado production is quite high in Indonesia led to increased waste avocado seed. Avocado seeds have an oil content large enough to potentially be used as a source of vegetable oil. A commonly used solvent for the extraction process is hexane. However, hexane proved to have an alarming danger if it is used for the extraction of food ingredients, necessitating alternative solvents such as n-heptane. This study was conducted to evaluate the effect of variable research on avocado seed oil extraction using n-heptane. The method used in this study is Response Surface Methodology-Central Composite Design (RSM-CCD) by varying the time of extraction, extraction temperature, avocado seed mass and volume of the solvent n-heptane. ANOVA with 95% confidence level (p <0.05) showed that the variables have a significant influence on the yield of avocado seed oil produced by the value of R2 = 94.24% at constant temperature and R2 = 93.95% at constant time. Characteristics of avocado seed oil is a orange color, density amounted to 0.71 g/ml, viscosity amounted to 0.43 cP, and FFA amounted to 2.76%. Analysis of fatty acid composition of avocado seed oil showed fatty acid component is predominantly polyunsaturated fatty acids as linoleic acid of 47.3531% (w/w), saturated fatty acids such as palmitic acid amounted to 20.3439% (w/w), and monounsaturated fatty acids as oleic acid amounted to 15.8823% (w/w).